Dynamics of Devaluation and "Equivalent" Fiscal Policies for a Small Open Economy. (IMF Working Papers; Working Paper ;, 1989)
In pursuing a steady-state reserve target, policymakers in small open economies can resort to devaluation or to temporary increases in public saving. This paper contrasts the dynamic implications of these alternative policies in a model with optimizing agents who possess perfect foresight. In general, the private sector cannot be insulated from the effects of the government's reserve-accumulation policies. The dynamic effects of devaluation depend on the fiscal policy rule in effect. In contrast to devaluation, the 'equivalent' fiscal policies imply discontinuities in private consumption and temporary tax increases may cause key macroeconomic variables to overshoot their steady-state values.